Circular Economy Ownership Models:A View From South Africa Industry - Al Amin , Mohamed Sultan (Elsevier B.V, 2016)
The world is neither globally successful in remanufacturing and re-use of products nor recycling of waste materials. This requires a combination of circular economy management systems,business models and novel technologies.There are contrasting views in literature regarding models for a circular economy.The main views are built on extended producer responsibility and on the role of end users.This paper is based on a study of the South African industry’s view of circular economy models,drivers and sustainers,with particular focus on composite waste. Cost reduction was found to be the strongest driver and sustainer for recycling of composites.Thus,maximizing opportunities to reduce cost is a key factor in encouraging South African companies to embrace the circular economy.This is important in developing appropriate national models for managing the transition to a circular economy.